Synergistic Effects of Multiple Non-Native Species and Phenotypic Plasticity Facilitate the Establishment of Yellow Catfish (Pelteobagrus fulvidraco) in Lake Erhai, a Subtropical Plateau Lake: Trophic Expansion and Robust Body Condition - Chuanyan Zhong; Zhuanxing Shao; Weile Chu; Jimeng Feng; Jian Shen; Xinze Wang; Xiaowen Long (Fishes, 2026)
The successful establishment of non-native fish often relies on life-history plasticity and opportunistic trophic strategies. This study elucidates the invasion mechanisms of the non-native yellow catfish (Pelteobagrus fulvidraco) in Lake Erhai, a plateau lake in China, by integrating morphometrics, stable isotope analysis, and DNA metabarcoding. Our results reveal a “triple mechanism” driving this invasion success. First, the population exhibits significant phenotypic plasticity, manifesting as enhanced somatic growth and superior body condition (mean condition factor: 1.92) and sexually dimorphic growth favoring males. Second, DNA metabarcoding confirms a broad trophic niche dominated by zooplankton (31.70%) and, critically, other non-native fishes (Hypomesus nipponensis and Neosalanx taihuensis), providing strong empirical support for the synergistic effects of multiple non-native species. This predation on high-energy forage fish likely fuels the observed somatic growth and high reproductive output, counteracting the typical size-reduction trade-offs often seen in biological invasions. Third, reproductive assessment indicates a protracted spawning period (spanning at least from spring through summer) and an absolute fecundity (mean: 8471 ± 2194 eggs) consistent with its strategy of producing larger, high-quality eggs, significantly exceeding that of native riverine populations. These findings suggest that P. fulvidraco effectively exploits altered food webs—specifically pre-existing invasive prey—to maximize somatic growth and reproductive output, thereby establishing dominance in the plateau lake ecosystem. Therefore, effective management strategies must go beyond single-species control and prioritize controlling pre-existing invasive forage fish to disrupt the facilitation pathway driven by ecosystem alteration by invasive species.